Perceived Organizational Support dengan Psychological Well-Being Pada Karyawan Perusahaan - Astrid Maria Lasamahu; Arthur Huwae (Bulletin of Counseling and Psychotherapy, 2022)
Society 5.0 emphasizes that technology and its functions are parts of human life and that human resources or employees are one of the most important parts of technological and industrial progress. In order to achieve better progress in an industry, the importance of perceived organizational support for the psychological well-being of employees working in the industry is significant. The purpose of the present study is to examine the effect of perceived organizational support on the psychological well-being of employees. The study employed the correlational quantitative method with a quota sampling technique. There were 52 participants who were employees of the company. The study used the scale of perceived organizational support (α = 0.880) compiled by researchers based on the theory of Eisenberger et al. (2002). The scale of psychological well-being (α = 0.917) compiled by Fadhil (2021) based on the theory developed by Ryff (1989) was also used. Data analysis results showed a correlation coefficient r of 0.218 with sig. = 0.120 (p>0.05), indicating that perceived organizational support had no significant effect on the employees’ psychological well-being because it was caused by other factors.